Activating Open Science Communities in Göttingen: From Policies to Real Meet-Ups - Schmidt, Birgit (Septentrio Conference Series, 2018)
Watch the VIDEO. Over the last two decades several research institutions have created policies which target Open Access to publications and research data, and are now moving on to Open Science from a wider perspective. These policies formulate an ambition with references to reality. This reality might look good on paper however, the challenge is to make this vision work at the individual and research group level. One way to bring these visions forward is to activate and grow a network of institutional Open Science practitioners and enthusiasts – by involving researchers, librarians, research managers/administrators and others, and creating opportunities for exchange and collaboration. In particular early career researchers will have very concrete ideas on what works for them, what is missing and what their challenges are when stepping into Open Science practices. The University of Göttingen is committed to make research results accessible and reusable for academia and the wider society. Its revised OA policy dates from 2016 (the first version dates from 2005) and the research data policy from 2014 [1].These policies serve as a reference point for desired practices as well as existing and emerging service areas. However, often these policies may not play an explicit role in researchers’ day-to-day practices – some elements may already be part of “normal science” while others have not been fully implemented yet. The presentation will focus on the practical vision and establishment of the Göttingen Open Science Meet-ups [2], as well as experiences and lessons learned from nearly two years of operation (at the time of the Munin conference). The initiative was launched in Autumn 2016 by a group of librarians. We will elaborate on how we reach out to and work with early career researchers, and what types of meetings are requested, e.g. informal technology-focused meetings (Hacky Hour Göttingen [3]). Moreover, we will provide some insight into how the sessions facilitate learning together and from each other (both in terms of topics as well as mind sets). From the library perspective there are also opportunities to link Open Science learning to service areas, in particular where new demands emerge, and to make existing services better known. Last, but not least, the Open Science network facilitated by these meet-ups provides opportunities to better link institutional policies with researchers’ practices – in particular, through discussions on opportunities and how to overcome obstacles as well as how to increase benefits and incentives. To this end, although the meet-ups mainly aim at strengthening a bottom-up approach, they also provide opportunities to inspire next steps for Open Science from a leadership perspective and to lift emerging good practices to a higher level.